2022
DOI: 10.1063/5.0074724
|View full text |Cite
|
Sign up to set email alerts
|

Super-resolution reconstruction of turbulent flow fields at various Reynolds numbers based on generative adversarial networks

Abstract: This study presents a deep learning-based framework to recover high-resolution turbulent velocity fields from extremely low-resolution data at various Reynolds numbers by utilizing the concept of generative adversarial networks. A multiscale enhanced super-resolution generative adversarial network is applied as a model to reconstruct the high-resolution velocity fields, and direct numerical simulation data of turbulent channel flow with large longitudinal ribs at various Reynolds numbers are used to evaluate t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(17 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…More details for MSP can be found in Yousif et al. (2021, 2022 b ). The outputs of the three submodels are summed and passed through a final convolutional layer to generate HR artificial data .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…More details for MSP can be found in Yousif et al. (2021, 2022 b ). The outputs of the three submodels are summed and passed through a final convolutional layer to generate HR artificial data .…”
Section: Methodsmentioning
confidence: 99%
“…(Goodfellow et al 2014) have shown great success in image transformation and super-resolution problems (Mirza & Osindero 2014;Ledig et al 2017;Zhu et al 2017;Wang et al 2018). Generative adversarial network-based models have also shown promising results in reconstructing HR turbulent flow fields from coarse data (Fukami et al 2019a;Fukami, Fukagata & Taira 2021;Güemes et al 2021;Kim et al 2021;Yousif et al , 2022bYu et al 2022). In a GAN model that is used for image generation, two adversarial neural networks called the generator (G) and the discriminator (D) compete with each other.…”
Section: Masked Multiheadmentioning
confidence: 99%
See 2 more Smart Citations
“…The MSP, which consists of three parallel 3D convolutional sub-models with different kernel sizes, is applied to the data features extracted by the RRDBs. More details regarding MSP can be found in Yousif et al 29 , 30 . The outputs of the three sub-models are summed and passed through a final 3D convolutional layer to generate an artificial 3D data ( ).…”
Section: Methodsmentioning
confidence: 99%